ВПЛИВ СПЕКТРУ СТРУМУ ЖИВЛЕННЯ НА ПУЛЬСАЦІЇ ОБЕРТАЛЬНОГО МОМЕНТУ БЕЗПАЗОВОГО МОМЕНТНОГО ДВИГУНА З ПОСТІЙНИМИ МАГНІТАМИ - Пєтухов, І.С.; Кіреєв, В.Г.; Акінін, К.П.; Лавриненко, В.А. (Інститут електродинаміки НАН України, Київ, 2025)
rotor was studied. The mode of feeding with a sinusoidal current, as well as the mode with injection into the higher harmonic current, are considered. The torque was calculated according to the static model of the magnetic field. It was determined that under the conditions of power supply with a sinusoidal current, there is a significant contribution of the sixth harmonic in the pulsations of the torque. The method of suppressing torque pulsations by injecting higher harmonics into the supply current was studied. It is shown that under the conditions of the amplitude of the pulsations of the rotational moment of the sixth harmonic of about 4%, the injection of the fifth harmonic with an amplitude of 2% of the fundamental into the current allows the reduction the pulsations by more than 10 times. References 10, figures 6, tables 1.